Concurrent Occurrence of Aneurysmal Bone Cyst and Fibrous Dysplasia in the Mandibular Bone of a Neonatal Calf - Eroksuz, Yesari; Incili, Canan Akdeniz; Tanrisever, Murat; Eroksuz, Hatice (Kafkas Univ, Veteriner Fakultesi Dergisi, 2024)
This report documents the simultaneous occurrence of aneurysmal bone cysts and fibrous dysplasia in a neonatal calf's mandibular bone. The mandibular bones exhibited significant protrusion, cystic cavities, and thin woven bone spicules. Additionally, the bone trabeculae were underdeveloped with necrotic changes, and there was an absence of bone marrow and osteoblastic rimming in the woven bone. Aneurysmal bone cysts were characterized by blood-filled cystic spaces lacking epithelial or endothelial cells, separated by fibroblastic septa. In conclusion, a unique case of mandibular fibrous dysplasia displaying certain similarities to cherubism and ABC has been recorded in a calf.
Keywords: Aneurysmal bone cyst; Bovine; Congenital fibrous dysplasia; Mandibular bone